Analisis Sifat Mekanis Beton Mutu Normal dengan Pemakaian Fly Ash lebih dari 50% dan Superplasticizer - Mahaningtyas, Erwin; , Dr. Mochamad Solikin (2016)
Concrete always get connected in every aspect of construction. Concrete is a composite material consisting of coarse and fine aggregate that is mixed with water and cement as a binder and filler coarse and fine aggregate, sometimes added additive or admixture when needed. The research's porpuse is to replace some of the cement material with the coal waste of Electric Steam Power Plant that is called fly ash. By making use of fly ash as a partial replecement of cement is considered to reduce enviromental pollution and in terms of budget is also more economical. The porpuse of the research is to know the ratio between the normal concrete and the concrete that is filled with the variation of fly ash 50%, 60% and 70% of the weight of the binder. The specimen that is used in the research is cylinder with the 15 cm diameter and 30 cm height for the compressive strength and tensile side strength, while for the concrete water absorption test the cylinder is used with the 10 cm diameter and 5 cm height. The compressive strength testing performed at the age 28 days and 56 days, while the tensile strength sides and water absorption test performed at the age 56 days. The method used in the concrete mix in accordance with ACI. f'c plan is 25 Mpa. Variations fly ash used in the research 50%, 60%, 70%. Fly ash used is class F fly ash. After testing get the result average compressive strength at 28 days produces the optimum value of 22.505 MPa at additional levels of fly ash of 50% as compared to the results do also test normal concrete with the results of 21.090 MPa, while at the age of 56 day compressive strength optimum that is in normal concrete amounted to 30.573 MPa the more levels of fly ash as well decreases the value of compressive strength, compressive strength at the age of 56 days can achieve the planned compressive strength of 25 MPa. The average tensile side strength obtained produces comparable value between normal concrete and concrete using fly ash variation of 50%, 60% and 70%. The more fly ash decreases the tensile side strength values. However, the decline was not significant. Average water absorption were obtained on normal concrete is 4.128%, with high levels of fly ash of 50% amounting to 3.575%, the levels of fly ash of 60% amounting to 3,239 and on the levels of fly ash of 70% amounting to 3.021 thus the normal concrete can more easily absorb water compared with the use of high volume fly ash.